Add 6x+5y-9xy and y-10x+3xy and then subtract -2x+5y-4xy from the sum.
Answers
Answered by
5
Step-by-step explanation:
6x+5y- 9xy +(y-10x+3xy)-(-2x+5y-4xy)
6x+5y-9xy+y-10x+3xy
(-4x+6y-6xy) - (-2x+5y-4xy)
(-4x+6y-6xy+2x-5y+4xy)
-2x+y-2xy
If you are satisfied from my answer
PLEASE MARK ME AS BRAINLIEST
I want to push my rank in brainly and I need 5 BRAINLIEST tags .
Answered by
2
Answer:
-2x+y-2xy
Step-by-step explanation:
6x+5y-9xy + y-10x+3xy
= 6x+(-10x)+5y+y+(-9xy)+3xy
=-4x+6y-6xy
Now, -4x+6y-6xy-{(-2x)+5y-4xy
=-4x-(-2x)+6y-5y-6xy-(-4xy)
=-4x+2x+y-6xy+4xy
=-2x+y-2xy
Similar questions